Developing Kataligen (A Multiple Intelligences-Based Hand Puppet) for a Group at ABA 1 Kindergarten, Kaliwates, Jember in 2019/2020 Academic Year - Igrah Lishantya Gusman; Nanik Yuliati; Luh Putu Indah Budyawati (Pancaran Pendidikan, 2019)
<p/ align="justify">This research is motivated by a number of children who are less focused on paying attention to the learning material when the teacher explains the material in the classroom. It is also to maximize the use of learning support media such as Educational Game Equipment (EGE) that support the development of the nine intelligences of children. This research was conducted to develop cataligent media (hand puppet based on multiple intelligences) group A in TK ABA 1 Kaliwates Sub-district, Jember Regency in Academic Year 2019/2020. The process and the result of media development of hand puppet based on multiple intelligences covering the nine intelligences: verbal-linguistic intelligence, logical-mathematical intelligence, spatial-visual intelligence, bodily-kinesthetic intelligence, musical intelligence, spiritual intelligence, interpersonal intelligence, intrapersonal intelligence, and naturalist intelligence. The purpose of this study was to develop the process and the result of media development which were obtained from cataligent media toward group A TK ABA 1 Kaliwates Sub-district, Jember Regency. This developmental research was conducted in the odd semester. The theory used in this research was the theory from Borg and Garl that is Research and Development (RnD). The data collection techniques used in this research was observation, validation, interviews, and questionnaires. The result showed that the development of kataligen media (hand puppet based on multiple intelligences) group A in TK ABA 1 Kaliwates Sub-district, Jember Regency, can be claimed effective. It is proven by the result of calculating the overall percentage of the result of observations toward children's activities that is 91.94%. Based on the result of the effectiveness of the first and the second day trials in group A1 showed that the children develop 2.78% in multiple intelligences of children. Based on this research, it is better to utilize appropriate learning media to develop multiple intelligences of children in order to facilitate students in teaching and learning process